Lou Andreas von Salomé e il fiabesco nel Weihnachtsmärchen - Paolo Levrero (Studi sulla Formazione)
The article aims to examine the fairy tail Weihnachtsmärchen - that is the Fiaba per il Natale, in Italian translation -, written in 1907 by Lou Andreas von Salomé, one of the most effervescent and libertarian intellectual figures in late Nineteenth and early Twentieth century in Europe. Through the codes of the imaginary and the fantastic typical of the fairy tale, Salomé constitutes an ontology and a poetics of childhood in which delicacy, enchantment and wonder preserve the mystery of life, which, in the metaphor of Christmas remembered in the story, sustains the existence of the child in his thoughtful walk in the world.